THE EXISTENCE OF CUSTOMARY LAND IN BALI AFTER THE APPOINTMENT OF CUSTOMARY VILLAGES AS SUBJECTS OF COMMUNAL PROPERTY RIGHTS OVER LAND - I Nyoman Yoga Narayana (NOTARIIL Jurnal Kenotariatan, 2023)
Customary land is land owned by indigenous peoples for generations since ancient times, in 2017 customary villages as a unit of indigenous peoples obtained property rights to land that provide legal certainty over customary land ownership but will also have an impact on the integrity of customary land in the future because property rights can be transferred and transferred to other parties. The purpose of this study is to be able to analyze strategies to maintain the Existence of Customary Land in BaliThis writing is normative legal research, namely research that examines the applicable positive legal norms, which are in the form of laws and regulations related to the existence of customary land in Bali after the appointment of customary villages as subjects of communal property rights to land, which focuses on land rights that are most appropriately owned by Customary Villages together with indigenous peoples, by using a statutory approach and a conceptual approach. The Property Rights were granted to the Indigenous Village.